THE PATTERN OF TURN TALKING ON VINDES YOUTUBE VIDEO EPISODE NAJWA SHIHAB TERLALU BERANI! VINCENT DESTA YANG TAKUT! - Guspita, Merlina (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2023)
This study aims to identify, classify, and analyze speech switching patterns in how to take turns in speaking contained in Vindes' YouTube video episode "Najwa Shihab Was So Brave! VincentDesta Who Were Frightened ". This research is included in qualitative research with descriptive methods using listening and recording techniques. The data used in this study are some sentences from the conversation between Vincent, Desta, and Najwa Shibah in Vindes' YouTube video episode "Najwa Shihab Was So Brave! Vincent Desta Who Were Frightened ". The results showed various patterns of speech transfer how to take turns in speaking contained in the video, namely 23 consisting of 1 by obtaining, 9 by stealing, 4 by grabbing, 6 by replacing, 2 by creating, and 1 by continuing.